2017
DOI: 10.1097/moh.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of histone H3, lysine 4 methyltransferases in normal and malignant hematopoiesis

Abstract: Purpose of review Histone H3, lysine 4 methylation (H3K4me) is one chromatin modification that defines distinct regulatory states of euchromatin. Mammals express 6 main histone methyltransferase enzymes (HMTs) that modify H3K4 by mono-, di-, or tri-methylation. Recent studies examine roles of some of these HMTs and their cofactors in hematopoiesis and leukemia. We discuss these emerging studies together with prior embryonic stem (ES) data revealing how these enzymes function. Recent findings Murine models ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 63 publications
(78 reference statements)
2
30
0
Order By: Relevance
“…Loss of Dpy30 results in the accumulation of hematopoietic stem and progenitor cells, while peripheral cells are depleted. This is consistent with the analysis of Mll1, which indicated that this MTase is required for proper development of the hematopoietic system [ 73 ]. Thus, the components of the WRAD complex, which have been analyzed thus far by knockout studies, are essential for mouse and/or organ development.…”
Section: Kmt2 Complexes Are Essential For Development and Are Affesupporting
confidence: 92%
See 1 more Smart Citation
“…Loss of Dpy30 results in the accumulation of hematopoietic stem and progenitor cells, while peripheral cells are depleted. This is consistent with the analysis of Mll1, which indicated that this MTase is required for proper development of the hematopoietic system [ 73 ]. Thus, the components of the WRAD complex, which have been analyzed thus far by knockout studies, are essential for mouse and/or organ development.…”
Section: Kmt2 Complexes Are Essential For Development and Are Affesupporting
confidence: 92%
“…The recombinant A/B complexes are predominantly mono- and di-methylating H3K4 with low tri-methylation activity [ 72 ]. In cells, however, these complexes are important for H3K4me3 [ 73 ]. The C/D complexes are preferentially mono-methylating H3K4 [ 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Methylation Of Histone H3 At Lysinementioning
confidence: 99%
“…Concomitant SET1A and SETD1B localization appears as largely nonoverlapping puncta along the euchromatin in the nucleus, suggesting that each protein binds to a unique set of target genes, thereby making nonredundant contributions to the epigenetic control of chromatin structure and gene expression . The mixed lineage leukemia ( MLL ) family of proteins (including MLL1‐MLL4 , SET1A and SETD1B ) specifically methylatesLys4 of histone H3 and plays a pivotal role in the transcriptional regulation of genes involved in hematopoiesis and development . Recent studies have provided evidence that TP53 is the target of SET1/COMPASS and have suggested that these genes may cooperate and function as a tumor suppressor .…”
Section: Discussionmentioning
confidence: 99%
“…The common CRs in cancer were found to be enriched mostly in readers and writers for histone modification and chromatin remodelers (19%, 56% and 19%, Supplementary Figure S12 ). Among these CRs, we identified some well-known oncogenes, such as KMT2C, SMARCD1 and SMARCA4 ( 1 , 33 , 38 ). For cancer-specific CRs, we found that these CRs included 36% of the DNA methylation erasers and 35% of the histone modification erasers.…”
Section: Resultsmentioning
confidence: 99%